(untitled) (Innovative professional education, 2025)
The article examines the using of digital technologies in the training of qualified workers in the mechanical engineering sector. Modern approaches to organizing the educational process are analyzed, including the application of software, online resources, video lessons, and virtual simulators. Using the example of the Kryvyi Rih Center of Vocational Education in Metallurgy and Mechanical Engineering, the study explores blended learning practices and the using of platforms such as Google Classroom, Google Drive, and additional resources such as Profosvita. It is emphasized that despite the challenges of wartime, practical training continues to take place offline in the institution’s training workshops. Digital resources are created to host relevant educational materials for students who study remotely. The prospects for the development of digital technologies in vocational education and their impact on the quality of specialist training are identified.